IJEN CAR FREE DAY: Gelanggang Olahraga Imajiner di Kota Malang - Indhar Wahyu Wira Harjo (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2020)
The availability of sports facilities and the number of residents in Malang shows a lack of balance in proportion. The government of Malang city has made some attempts to collaborate with any parties to allocate the proportional sports facilities for the residents. To deal with the problem, the government has designed a program called Ijen Car Free Day (ICFD) as one alternative of solutions. The Ijen Street, which mostly functions as the main street, has also served as a sport center. The present study aims at investigating the utilization of roads of Ijen Street as one of sports centers. The analysis is carried out to re-observe the use of public space that has experienced some transformations. The data collected are examined thoroughly by implementing the research method of descriptive qualitative. The result of the study indicates that the Ijen Street is a sterile road section of motor vehicles at 06:00 up to 10:00, and during the time, the road is used for some sports activities. The so-called elite region of Malang city has transformed into courts for morning gymnastics and jogging tracks along the way. In addition, the area is also used as a social, economic, and cultural spaces. The visitors of Ijen CFD often takes the chance to sell some products, join some communities, and perform some shows of art and culture. The comprehension of the models of space use is necessary to optimize the management of Ijen CFD in the future. Proporsi ketersediaan fasilitas olahraga dengan jumlah penduduk di Kota Malang memperlihatkan ketimpangan. Pemerintah Kota Malang berupaya melakukan kerja sama dengan berbagai pihak untuk menyediakan fasilitas olahraga yang proporsional bagi warga. Untuk mengatasi permasalahan tersebut, Pemerintah Kota Malang merancang Program Ijen Car Free Day (ICFD) sebagai alternatif solusi dengan mengalihfungsikan Jalan Besar Ijen sebagai wahana olahraga. Penelitian ini menelaah penggunaan ruas Jalan Besar Ijen sebagai gelanggang olahraga. Telaah tersebut untuk meninjau kembali penggunaan ruang publik yang mengalami transformasi pemanfaatan. Data diulas menggunakan metode penelitian kualitatif deskriptif. Hasil penelitian menunjukkan bahwa kawasan Jalan Ijen menjadi ruas jalan yang steril dari kendaraan bermotor sejak pukul 06.00 hingga 10.00. Di rentang waktu itu, jalan raya dimanfaatkan untuk ruang olahraga. Sepanjang kawasan itu berubah menjadi ‘lapangan’ untuk senam pagi, joging track, atau jalan santai. Selain itu, kawasan tersebut juga digunakan sebagai ruang sosial, ekonomi dan budaya. Para pengunjung ICFD acapkali menggunakan kesempatan itu untuk berjualan, berkumpul dengan komunitas, dan melakukan pertunjukan seni-budaya. Pemahaman terhadap model-model penggunaan ruang tersebut diperlukan untuk mengoptimalkan pengelolaan Ijen CFD.